Chemical Composition, Total Phenolic Content, and Anti-Ulcerative Colitis Effects of Extract and Essential Oil of Cupressus arizonica Greene Fruits - Mohammad Bagher Majnooni; Saeid Mohammadi; Gholamreza Bahrami; Ehsan Mohammadi-Noori; Mohammad Hosein Farzaei (Tehran University of Medical Sciences, 2022)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease, which has a global prevalence. Also, the plants of the Cupressaceae family have prominent anti-inflammatory and wound healing effects, so they can be considered as promising candidates for the treatment of UC. In this study, the therapeutic effects of extract and essential oil of Cupressus arizonica Greene (C. arizonica) fruits in the animal model of UC were investigated. Total of 35 Wistar male rats were treated with essential oil and hydroalcoholic extract for one week after induction of colitis by acetic acid. The colonic segment cut for macroscopic and histological analysis. The total amount of extract phenol and flavonoid content was assayed by Folin-Ciocalteu and aluminum chloride colorimetric method, respectively. The essential oil was analyzed by gas chromatography/mass spectrometer (GC/MS). The extract at doses of 100 mg/kg and 250 mg/kg and essential oil at doses of 0.5 mg/kg showed significant effects on UC (P < 0.05). The total phenolic content of hydroalcoholic extract in terms of mg of gallic acid/ g of extract was 191.625 ± 7.04 and the amount of total flavonoids in terms of mg of rutin/g of extract was 66.52 ± 6.51. Also, according to the results of GC/MS analysis, α-pinene was the major constituent of essential oil. Our results revealed that the extract and essential oil of C. arizonica fruits had therapeutic effects on UC, and this effect may be related to the presence of polyphenolic and terpene compounds.